Dynamic in vivo monitoring of fracture healing process in response to magnesium implant with multimodal imaging: pilot longitudinal study in a rat external fixation model. (16th February 2022) - Sun, Yu; Helmholz, Heike; Will, Olga; Damm, Timo; Wiese, Björn; Luczak, Monika; Peschke, Eva; Luthringer-Feyerabend, Bérengère; Ebel, Thomas; Hövener, Jan-Bernd; Glüer, Claus-Christian; Willumeit-Römer, Regine
Abstract : This study introduced a rat model for preclinical investigation of magnesium-based biodegradable materials in bone fracture conditions, allowing longitudinal in vivo monitoring of fracture healing and implant degradation with multimodal imaging. Abstract : Rodent models are commonly used in pre-clinical research of magnesium (Mg)-based and other types of biomaterials for fracture treatment. Most studies selected unstable fixation methods, and there is a lack of multimodal longitudinal in vivo monitoring of bone healing. The purpose of this study is to develop a rat femoral fracture model stabilized by external fixation with intra-medullary Mg implant, and to investigate the dynamic bone union process with several imaging techniques offering complementing insights into the process. Pure Mg pins were prepared, followed by an in vitro degradation test. Male Sprague-Dawley rats in the experimental group underwent femoral osteotomy stabilized by external fixators with intra-medullary implantation of Mg pins, and the control group underwent external fixation without intra-medullary implants. Post-operative radiograph, micro-CT and B-mode ultrasonography were acquired directly after surgery, and re-examined at week 4, 8 and 12. Bone tissue volume, in vivo implant degradation, histological staining and MRI images were analyzed using ex vivo samples. Both groups achieved fracture union at week 12, and the dynamic healing process was illustrated by in vivo radiograph, micro-CT and ultrasonography. Bilateral whole femur ex vivo analysis further demonstrated increased ratio of bone tissue volume in the surgical femur with Mg implants, and in vivo degradation of Mg pins was slower than in vitro results. Titanium screws rather than intra-medullary Mg pins were the source of artifact in MRI. This pilot study showed the rat fracture model with external fixation and intra-medullary Mg implantation to be an effective method for dynamic in vivo monitoring of the bone healing process. Future application of the animal model may facilitate pre-clinical translational research of biodegradable orthopaedic implant materials for fracture treatment.